أﺳﺑﺎب ﺗﺄﺧر اﻧﺟﺎز اﻟﻣﻌﺎﻣﻼت /اﻟروﺗﯾن ﻓﻲ وزارة اﻟﺗرﺑﯾﺔ ﻣن وﺟﮭﺔ ﻧظر ﻣدﯾري اﻷﻗﺳﺎم ورؤﺳﺎء اﻟﺷﻌب (Journal of the College of Education for Women, 2019)
Focused research problem that every work of any kind or size has signs indicating it and reveal the nature of either positive aims to achieve the objectives of the organization or a negative intersects with and contrasts with the context and style is the of work, as much as we care to fulfill the positive initiatives and seek to activate it and it to expect of them development of work and approach of the target by most direct route, we should take care also and just the sane, if not larger by indicators and negative actions because it is the way and means to detect imbalances cases that prevent achieving the desired objectives, or cause waste of money, effort, time, and therefore dispersion energies, efforts and wasted resources without result, so good management and successful should seek permanently to assess the reality of the organization in terms of the existence of cases of delayed completion of the procedures (routine) to be addressed first off to prevent escalation and limit their spread through indicators and evidences, which reflects it is the concept on the truth of the Organization under the influence of This phenomenon, which can be summarized as follows: 1 - What is routine? And how it changed to a phenomenon inherent to the government departments in general and the Iraqi Ministry of Education in particular? 2 - What causes the phenomenon of delayed completion of the procedures (red tape) in the departments of the Ministry of Education? 3 - What the proposed solutions to the problems caused by delay in completing the transaction (routine) to overcome these problems? Derived from the importance of research the following: 1-Classify Ministry of Education service ministries vital us one of, that serve a large segment of Iraqi society, includes teachers who form large staff in the Iraqi state, as well as they serve a group greater than and portion of them and equal with them in importance and vitalize or more, and that is a segment of students who are the nucleus of Iraqi or more society and builders of the future. And serve the primary responsibility which rests with the ministry. 2 - Consider routine phenomenon most prevalent in the Ministry of Education, and this phenomenon is not determined by a certain level, but include all job levels in the hierarchy. 3- The weakness of Ministry of Education in provision services and in a suits level of decent citizens, as there are many obstacles and difficulties in the way of completion of transactions of the citizens before them. One was The objectives of the research including the following: 1-Identify the phenomenon of routine and to clarify the causes and dimensions and factors associated with them. 2-Provide solutions and remedies to the phenomenon of red tape to senior management and subordinates in the Ministry of Education. Consists of the research community the total of the managers of departments and heads of the sub department in the Directorates General for Education in the province of Baghdad (Karkh, Rusafa), as well as the province of Nineveh, Random sample was selected from the department managers numbered (165) Director representing the percentage (100%) of the indigenous community, either the heads of the people bringing the number (240) Head of Division, representing the percentage (57%) of the indigenous community used the resolution of open and closed tool to collect data Lovers Find reasons for delay in completion of transactions are as follows: 1-Technological reasons. 2-Administrative reasons. 3-Legal reasons. 4-Personal reasons. The most important conclusions of theresearch: 1 - The ambiguity of some legislation and laws, it is still a lot of concepts and principles of law is not precisely defined sense, descriptive or procedural, putting these laws to the many explanations harm or hinder the completion of transactions of the citizens. 2 - The ignorance of most of the staff regulations and rules and regulations of administrative and financial officer, making the cause of routine or involved in it. 3- Low professional capacity of workers, and low technical skills of some workers, due to a lack of training courses and the weakness of the scientific content of these training courses. 4 - Weakness and limitation systems of work force, where they are doing business in the various departments of state government application (work systems) obsolete and backward in terms of structural and functional The main recommendations were as follows: 1 - Review of the administrative system current for the various components by adopting a new philosophy of management focus on strategic planning and quality of output and efficiency of resource use and reduce the size of the routine work of the Executive and the focus on efficiency and excellence in performance, and restructuring the administrative system and attention to the ways and tools of the administrative work effectively. -2 Insertion of e-government and modern programming that contribute significantly to resolve many of a series of revisions, and that due to the presence of all information at one side, and thus do not need to go and return from an employee to another, and reduces the e-government opportunities for corruption (such as bribery, nepotism , clientelism) and to reduce citizen contact with the staff, as well as reduce the number of papers required of the citizen, but only to submit the application. 3 - Building a functioning system of administrative control and performance evaluation methods and techniques appropriate and effective and to identify standards and performance planning and making the target efficiency, quality, productivity, and good use of resources and capabilities, and preservation of the basic criteria for evaluating performance.and Basra, the number of department managers in those districts (165) while the number of heads of the people (701) in the provinces (Baghdad, Basra, Nineveh) in (2010), 4 - Simplification of procedures, so that citizens pass by one employee in order to complete their application one employee, that employee has a legal and administrative procedures necessary to accomplish the task.